COVID-19 and international travel for sport. Important safety information (AIS, 2020)
Athletes have a natural desire to compete internationally in the 12 months preceding an Olympic/Paralympic Games. Athletes, coaches and sport organisations need to recognise however that in these extraordinary times, the potential risks of international travel may outweigh the perceived benefits. This document provides the current regulations around international travel from Australia and provides guidance and a checklist for sport organisations to consider in relation to International travel.